Connecting Openness and the Resting-State Brain Network: A Discover-Validate Approach - Wang, Junjie; Hu, Yang; Li, Hong; Ge, Ling; Li, Jing; Cheng, Long; Yang, Zhi; Zuo, Xinian; Xu, Yong (Frontiers in Neuroscience, 2018)
In recent years, the openness-brain association has been a topic of interest in the filed of personality neuroscience. Previous studies have usually been driven by openness trait and used it to infer brain functional activity characteristics, but no study has used a “brain-first” research strategy to explore that association based on more objective brain imaging data. In this study, we used a fully data-driven approach to discovery and validate the association between openness and the resting-state brain network. We collected data of 120 subjects as a discovery sample and 56 subjects as a validation sample. The Neuroticism Extraversion Openness Five-Factor Inventory (NEO-FFI) was used to measure the personality characteristics of all the subjects. Using an exploratory approach based on independent component analysis of resting-state fMRI data, we identified a parietal memory network that consisted of the precuneus and inferior parietal lobe. The inter-subject similarity of the parietal memory network exhibited significant associations with openness trait, and this association was validated using the 56-subject independent sample. This finding connects the openness trait to the characteristics of a neural network and helps to understand the underlying biology of the openness trait. In addition, combined with our previous research, we can partly support the viewpoint that personality is one of important factors in the pathogenesis of schizophrenia.